Insights into digital guidance: Reliability of self-assessment in youth-oriented Zekki Service - Reija Paananen; Sakari Kainulainen; Varpu Wiens; Joakim Zitting (Finnish Journal of eHealth and eWelfare)
This study's practical objective was to determine the reliability and feasibility of the service guidance based on the Traffic Light model used in the Zekki digital service. The equivalence between the numerical answers to the 3X10D Survey questions in Zekki and the young people's life situations was studied, revealing how well the Traffic Light model defined by the researchers matched the respondents' views. The equivalence of people's descriptions of their life situations was compared to their given quantitative assessments (N = 185). Based on written descriptions, the researcher classified each answer as a number. Equivalence was evaluated by cross-tabulating the researchers' and survey respondents' assessments of their life situations and testing the results with a chi-squared test. The respondents' assessments of satisfaction with different life spheres were compared with those made by the researchers, who read the written descriptions. Overall, the respondents' numerical assessments were slightly more positive than the researchers' assessments. However, two-thirds of the researchers' and respondents' assessments matched exactly within the same Traffic Light category. The assessments differed by no more than one category in about one-third of the cases. Only 3.5% of the assessments were considered completely incorrect. The 3X10D Survey produces numerical information strongly connected to a respondent's real life, making it a reliable basis for digital service guidance. The Zekki digital service recommends appropriate support for those in need. Based on these findings, other user-oriented digital service guidance platforms can be developed.